Influence Of Green Banking Disclosure, CAR And ROE On PER - Asrianingsih Putri; Anwar; Abdul Rahman; Anwar Ramli; Annisa Paramaswary (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
The banking sector plays a pivotal role in Indonesia's economy, yet during the 2020–2024 period, conventional banks experienced substantial fluctuations in firm value, as measured by the Price Earnings Ratio (PER). This study investigates the influence of Green Banking Disclosure (GBD), Capital Adequacy Ratio (CAR), and Return on Equity (ROE) on the firm value of conventional banks listed on the Indonesia Stock Exchange (IDX). Utilizing a quantitative panel data approach, the research analyzes 160 quarterly observations from eight banks over the study period using Eviews 13 software. The findings indicate that GBD does not significantly affect firm value, suggesting that sustainability disclosures have yet to be perceived as a critical signal by investors. Similarly, CAR shows no statistically significant impact, implying that capital adequacy is not a decisive factor in market valuation. In contrast, ROE demonstrates a positive and significant effect on PER, confirming that profitability serves as a strong signal to investors, in line with Signaling Theory. The model’s adjusted R-squared of 0.401 suggests that 40.12% of the variation in firm value can be explained by GBD, CAR, and ROE, while 59.88% is attributable to other factors beyond the study’s scope. These results highlight that in the Indonesian banking sector, firm value is primarily driven by financial performance rather than sustainability practices or capital adequacy. Therefore, banks are encouraged to enhance profitability to maintain investor confidence and strengthen market valuation, while continuing to develop green banking initiatives for long-term strategic positioning.